DEVELOPING ISLAMIC ELT MATERIALS FOR ELEMENTARY SCHOOLS: A CRITICAL PEDAGOGICAL FRAMEWORK - Windy Febriani (INSPIRATION: Instructional Practices in Language Education, 2026)
This study addresses the critical need for culturally and religiously responsive English Language Teaching (ELT) materials for Islamic elementary schools. It argues that mainstream ELT resources often neglect the Islamic worldview, creating a disconnect for young learners. The objective of this research is to establish a framework for developing Islamic ELT materials that not only teach English effectively but also integrate Islamic values, contexts, and knowledge through a critical pedagogical lens. Employing a qualitative design, the methodology includes a critical content analysis of existing textbooks and a thematic analysis of data gathered from interviews with teachers and curriculum experts in Indonesian Islamic elementary schools. The analysis revealed a significant gap in materials that meaningfully incorporate Islamic principles while adhering to modern language acquisition theories. The study proposes a set of principles for material development that promotes critical cultural awareness, uses authentic Islamic contexts, and fosters both linguistic and spiritual intelligence. The study suggests that such a framework has the potential to enhance learner engagement, identity affirmation, and educational relevance while contributing to ongoing discussions on localized and culturally responsive ELT practices.